Modelos microscópicos de herança no século XIX: a teoria das estirpes de Francis Galton - Polizello, Andreza (2009)
Francis Galton (1822-1911) made important contributions in several fields of science. Among other things, he was the founder of the Biometric School developed by Karl Pearson and Walter Frank Raphael Weldon. The aim of this dissertation is to discuss Galton s ideas on inheritance developed during the period between 1855 (when he published his first works on the subject) and 1889 (when he published the book Natural inheritance), especially focusing his theory of stirps (1872), taking into account the other microscopic models of inheritance proposed in the 19th century. Besides that, it will compare Galton s theory of stirps to Darwin s hypothesis of pangenesis. Moreover, it will try to detect if there were significant changes in Galton s thought concerning the subject during this period. It will also try to elucidate if the low impact received by the theory of stirps was due to a weak foundation. This dissertation contains an introduction and five chapters. Chapter 1 presents some microscopic models of inheritance which were proposed during the 19th century. Chapter 2 discusses Darwin s hypothesis of pangenesis and its test made by Galton. Chapter 3 analyses Galton s theory of stirps. Chapter 4 discusses about the development of Galton s theory of heredity from 1865 to 1892. Chapter 5 provides some final remarks on the subject. This study led to the conclusion that Galton s proposal presented some peculiarities which differentiated it from the other ones of his time such as the experimental test of pangenesis, the performance of several experiments with peas, dogs and the study of genealogies and in addition to this, his concern in giving a statistical treatment to the data. A comparison between his several works showed a continuity of his thoughts on heredity with no significant changes